SONOlysis in prevention of Brain InfaRctions During Internal carotid Endarterectomy (SONOBIRDIE) trial – study protocol for a randomized controlled trial. Issue 1 (December 2017) - Hrbáč, Tomáš; Netuka, David; Beneš, Vladimír; Nosáľ, Vladimír; Kešnerová, Petra; Tomek, Aleš; Fadrná, Táňa; Beneš, Vladimír; Fiedler, Jiří; Přibáň, Vladimír; Brozman, Miroslav; Langová, Kateřina; et al.
Abstract Background Carotid endarterectomy (CEA) is a beneficial procedure for selected patients with an internal carotid artery (ICA) stenosis. Surgical risk of CEA varies from between 2 and 15%. The aim of the study is to demonstrate the safety and effectiveness of sonolysis (continual transcranial Doppler monitoring, TCD) using a 2-MHz diagnostic probe with maximal diagnostic energy on the reduction of the incidence of stroke, transient ischemic attack (TIA) and brain infarction detected using magnetic resonance imaging (MRI) by the activation of the endogenous fibrinolytic system during CEA. Methods/design Design: a multicenter, randomized, double-blind, sham-controlled trial. Scope: international, multicenter trial for patients with at least 70% symptomatic or asymptomatic ICA stenosis undergoing CEA. Inclusion criteria: patients with symptomatic or asymptomatic ICA stenosis of at least 70% are candidates for CEA; a sufficient temporal bone window for TCD; aged 40–85 years, functionally independent; provision of signed informed consent. Randomization: consecutive patients will be assigned to the sonolysis or control (sham procedure) group by computer-generated 1:1 randomization. Prestudy calculations showed that a minimum of 704 patients in each group is needed to reach a significant difference with an alpha value of 0.05 (two-tailed) and a beta value of 0.8 assuming that 10% would be lost to follow-up or refuse to participate in the study (estimated 39 endpoints). Endpoints: the primary endpoint is the incidence of stroke or TIA during 30 days after CEA and the incidence of new ischemic lesions on brain MRI performed 24 h after CEA in the sonolysis and control groups. Secondary endpoints are occurrence of death, any stroke, or myocardial infarction within 30 days, changes in cognitive functions 1 year post procedure related to pretreatment scores, and number of new lesions and occurrence of new lesions ≥0.5 mL on post-procedural brain MRI. Analysis: descriptive statistics and linear/logistic multiple regression models will be performed. Clinical relevance will be measured as relative risk reduction, absolute risk reduction and the number needed to treat. Discussion Reduction of the periprocedural complications of CEA using sonolysis as a widely available and cheap method may significantly increase the safety of CEA and extend the indication criteria for CEA. Trial registration ClinicalTrials.gov, NCT02398734 . Registered on 20 March 2015.